Precise placement of thioester bonds into sequence-controlled polymers containing ABAC-type units - Yanni Xia; Tong Shao; Yue Sun; Jianuo Wang; Chaoyuan Gu; Chengjian Zhang; Xinghong Zhang (Nature Communications)
Abstract The precise placement of thioester bonds into sequence-controlled polymers remains a grand challenge. Here, we demonstrate the versatile synthesis of sequence-controlled polymers from the step polymerization of cyclic thioanhydrides (A), diacrylates (B), and diols/diamines (C). In addition to easily accessible diverse monomers, the method is metal-free/catalyst-free, atom-economical, and wide in monomer scope, yielding 107 polymers with >90% yields and weight-average molecular weights of up to 175.4 kDa. The obtained polymers contain ABAC-type repeating units and precisely distributed in-chain thioester and ester (and amide) groups. The chemoselectivity of the polymerization is revealed by density functional theory calculations. The polymer library exhibits considerably tunable performance: glass-transition temperatures of −36–72 °C, melting temperatures of 43–133 °C, degradability, thermoplastics/elastomers, and thioester-based functions. This study furnishes a facile method to precisely incorporate thioester bonds into sequence-controlled polymers.